Sagittal plane walking patterns are related to MRI changes over 18‐months in people with and without mild‐moderate hip osteoarthritis. Issue 5 (2nd November 2017) - Kumar, Deepak; Wyatt, Cory; Lee, Sonia; Okazaki, Narihiro; Chiba, Ko; Link, Thomas M.; Souza, Richard B.; Majumdar, Sharmila
ABSTRACT: The purpose was to evaluate the association of sagittal plane gait mechanics with MRI changes in the hip joint over 18‐months. Subjects with and without radiographic hip OA ( n  = 57) underwent MRI at baseline and 18 months for grading of cartilage lesions, bone marrow lesions (BML), cysts, and labral tears. 3D gait analyses at baseline were used for sagittal plane hip kinematics and kinetics during the stance phase. Subjects were classified as progressors or non‐progressors based on increase in any MRI OA parameter. Multivariate ANOVA were used for differences in sagittal gait parameters between progressors and non‐progressors at baseline while adjusting for age. Logistic regression was used to estimate the probability of being classified as a progressor or non‐progressor with increasing hip flexion while adjusting for age, BMI, sex, and presence of radiographic hip OA. Of the 57, 35 were classified as non‐progressors and 22 were classified as progressors. At baseline, the progressors walked with 4.5° greater hip flexion during early stance ( p  = 0.021) and 3.5° lesser hip extension in late stance that was nearly significant ( p  = 0.059). Walking with greater hip flexion at baseline was associated with a greater risk of increase in MRI defined structural changes in the hip joint (Odds Ratio = 1.1, p  = 0.038). Greater hip flexion during walking was associated with a risk of structural progression of hip OA. The results may guide future interventions to alter the walking patterns and slow structural hip OA progression.© 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1472–1477, 2018.